2018
DOI: 10.1071/hc18023
|View full text |Cite
|
Sign up to set email alerts
|

Local clinical pathways: from ‘good ideas’ to ‘practicality’ for general practitioners

Abstract: INTRODUCTION There has been increased interest in the utility of clinical pathways by primary health care in New Zealand, although evaluation of their use has been limited. AIM To identify barriers and facilitators for the use of clinical pathways in one health region. METHODS Interviews with 15 general practitioners in the Western Bay of Plenty. A qualitative thematic analysis was undertaken, informed by the Diffusion of Innovation Framework. RESULTS Four themes were identified: learning to use the pathways, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…Our findings support the results of previous qualitative studies that identified barriers and facilitators for using and implementing clinical pathways in healthcare settings [ 4 , 38 40 ]. For example, a qualitative study by Reyneke, et al [ 4 ] aimed to identify barriers and facilitators of general practitioners using clinical pathways in a primarily urban health region in New Zealand. The care pathways were web-based flow diagrams directing practitioners to treatment modalities available in the community.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings support the results of previous qualitative studies that identified barriers and facilitators for using and implementing clinical pathways in healthcare settings [ 4 , 38 40 ]. For example, a qualitative study by Reyneke, et al [ 4 ] aimed to identify barriers and facilitators of general practitioners using clinical pathways in a primarily urban health region in New Zealand. The care pathways were web-based flow diagrams directing practitioners to treatment modalities available in the community.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, care pathways support the mutual decision-making between patients and clinicians [ 2 ]. Conceptually, the growing body of literature supports the use of care pathways; however, their development and dissemination alone are not enough to meaningfully impact practice behaviour [ 3 , 4 ]. Significant individual, systems, and contextual barriers along with awareness and lack of familiarity may hinder the uptake of care pathways and associated clinical recommendations in practice settings [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Further relating to the practical use of guidelines, Reyneke, Jaye and Stokes examine the process of accepting and using care pathways in the Western Bay of Plenty. 14 We also have an array of papers about health care services. Nixon shows how point of care ultrasounds in rural hospitals influence generalist physicians' decision-making.…”
Section: Reading Writing and Research Impactmentioning
confidence: 99%
“…health.nz/about-us/key-projects-and-initiatives) has the potential to improve the quality of referrals, but there is currently no guideline within Healthpathways for mental health services. 18,19 There are also no New Zealand-based studies relating to the content and quality of referrals from primary care to specialist mental health services. The objective of this study was to evaluate content of referral letters, using an audit tool.…”
Section: Introductionmentioning
confidence: 99%